Optimal allocation of a wind turbine and battery energy storage systems in distribution networks based on the modified BES-optimizer - Kamel, Salah; Abdel-Mawgoud, Hussein; Alrashed, Mohammed M.; Nasrat, Loai; Elnaggar, Mohamed F. (Frontiers in Energy Research, 2023)
In the last few decades, incorporating renewable energy resources (RERs) such as photovoltaic (PV) and wind turbine (WT) in distribution network are rapidly increased to meet the load growth. However, distribution networks have been facing many challenges to withstand the intermittent and probabilistic output power of RERs. Battery energy storage (BES) is used with RERs to smoothly inject the output power to the grid by RERs. Therefore, this paper proposes an effective strategy for optimal allocation of WT and BES in RDS with the aim of decreasing the total system loss-es. In addition, a modified Bald eagle search (BES-Optimizer) is proposed and utilized to obtain the best sizing and locations of WT and BES sim-ultaneously in RDS considering the probabilistic of WT and load demand. IEEE 69-bus RDS is utilized as a test system with variable commercial load during 24-hours considering the system operating constraints. Based on the obtained results, installing WT with BES gives better results than installing WT alone in RDS. Also, installing multiple WT alone or with BES gives better results than installing single WT alone or with BES in RDS. However, the proposed algorithm proved its efficiency to obtain the best global results compared with other well-known techniques.